Evaluation of The Implementation of The Center of Excellence Smk Program in Vocational High Schools - Pajow, Lidyanti N.; Lengkong, Jeffry SJ; Sumampouw, Zoya F. (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study aims to analyze and evaluate the implementation of the Center of Excellence vocational high school program at SMK Negeri 1 Ratahan. The research method used is the CIPP model (context, input, process, product). The subjects of this study were the principal, the head of the program committee, the head of the Light Vehicle Engineering expertise program, several productive teachers, several students of the industrial program, the business world and the world of work. Data collection was carried out through interviews, observations and documentation. Based on the results of the discussion, it can be concluded that; 1) The evaluation of the program from the context aspect is stated to be very good and effective because it has been implemented in accordance with the legal basis, policies, and guidelines of the Directorate General of Vocational Education; 3) The evaluation of the program from the input aspect is stated to be very good and effective in terms of improving the quality of human resources in this case educators and students, the procurement of facilities/infrastructure that meets the standards of the world of work, and effective financing in supporting each component of the program; 2) The evaluation of the program from the process aspect is stated to be very good and effective in terms of the implementation process of internal teachers, students of field work practices, and industrial classes. Through partnerships with industrial programs, the business world and the world of work, the implementation of teaching and learning activities both in schools and in industry allows students to experience learning experiences as they work in the world of work, so that when they graduate they will become competent ready-to-use workers according to their field of expertise; 4) Evaluation of the program from the product aspect is stated to be good in terms of the absorption of graduates in the world of work. Based on the data collected, it was found that not 100 percent of students who graduated were immediately absorbed in the world of work. Although some continued to college and became entrepreneurs, of the graduates who had completed their education, there were still some who had not worked.